Serum Metabolomic Profiling to Reveal Potential Biomarkers for the Diagnosis of Fatty Liver Hemorrhagic Syndrome in Laying Hens - Guo, Lianying; Kuang, Jun; Zhuang, Yu; Jiang, Jialin; Shi, Yan; Huang, Cheng; Zhou, Changming; Xu, Puzhi; Liu, Ping; Wu, Cong; Hu, Guoliang; Guo, Xiaoquan (Frontiers in Physiology, 2021)
Fatty liver hemorrhage syndrome (FLHS), a nutritional and metabolic disease frequently occur in laying hens, causes serious losses to the poultry industry. While currently, the traditional clinical diagnosis of FLHS still has its limitations. Therefore, hunting for some metabolic biomarkers and elucidating the metabolic pathway in vivo will be a significant device for the diagnosis and prevention of FLHS. In the present study, a model of FLHS in laying hens induced by feeding a high-energy low-protein diet was established. GC-TOF-MS was used to analyze the metabolites in serum for 40 days and 80 days. The result showed that a total of 40 significant difference metabolites closely related to the occurrence and development of FLHS were screened and identified, which were mainly associated with lipid metabolism, amino acid metabolism, and energy metabolism pathway disorders. Further investigation of differential metabolite showed 10 potential biomarkers such as 3-hydroxybutyric acid, oleic acid, palmitoleic acid, and glutamate were possessed of higher diagnostic value by analyzing of receiver operating characteristic (ROC) curves. In conclusion, this study showed that the metabolomic method based on GC-TOF-MS can be used in the clinical diagnosis of FLHS in laying hens and provide potential biomarkers for early risk evaluation of FLHS and further insights into FLHS development.